An Unusual Presentation of Charcot Arthropathy Caused by Syringomyelia Mimicking a Soft Tissue Tumor - Cuneyd Gunay; Ebru Atalar; Baybars Ataoglu (Case Reports in Orthopedics)
Charcot arthropathy is a chronic, degenerative condition and is associated with decreased sensorial innervation. Numerous causes of this arthropathy have been described. Here we report a case of neuropathic arthropathy secondary to syringomyelia which was misdiagnosed as a soft tissue tumor and treated surgically and additionally with radiotherapy at another institution. The patient had clinical and radiological signs of syringomyelia, associated with a limited range of motion, swelling, and pain in the affected joint. Neuropathic arthropathy, although less common, should be considered in cases of unexplained joint swelling, pain, and limited range of motion of the affected joint.